(untitled) (Bangladesh Critical Care Journal, 2023)
Endometriosis is the presence of endometrial glands and stroma outside the uterus. Endometriosis is the commonest gynaecological problem; it affects 7 to 10% women in reproductive age group. Spontaneous abdominal wall endometriosis (AWE) is any ectopic endometrium found superficial to the peritoneum without the presence of any previous scar. In our case study, though the patient had a caesarean section, the endometriosis developed in unscarred area. It was located below the umbilicus in the midline, which is a common site for spontaneous abdominal endometriomas. Initially the patient had cyclic infra-umbilical pain, gradually it became constant and severe. Due to irregular follow up and unusual site and presentation of the lesion, it took a long time to diagnose the condition. During operation the mass was spotted in the midline and extend up to the peritoneum. It was taken out by wide local excision. Pathology revealed endometrial glands surrounded by a disintegrating mantle of endometrial stroma and fibrous scar tissue in which there was a scattering of leucocytes. Spontaneous AWE is rare, accounting for 20% of all AWEs. Spontaneous endometriomas are usually diagnosed by pathology and the treatment of choice is surgical excision Bangladesh Crit Care J March 2023; 11 (1): 51-53